Jónas Jónsson and his Precepts for Icelandic Art - Guðni Tómasson 1976- (2003)
MLitt ritgerð við School of Art History við St. Andrews háskóla í Skotlandi In the first half of the 20th century attempts were made by political forces in Europe to utilize the visual arts to develop the nationalistic sentiments of the citizens of several countries. The most famous example of this is the German one, where the Nazi regime promoted certain artists while it suppressed and attacked others. Another example, and a lot less known internationally, were attempts made by Icelandic politician Jónas Jónsson to influence the artistic output of Icelandic artists in the beginning of the 1940s. These took place shortly before Iceland became fully independent from Danish rule. In addition to his writings on the subject, Jónsson also used methods similar to those in Germany of exhibiting works that he deemed “acceptable” and “unacceptable” in the output of several Icelandic visual artists. Although these exhibitions and the disputes that arose between Jónsson and a group of Icelandic artists were in part an answer to the criticism that the artists put forth against Jónsson and his Board of Education, they were mainly a struggle about the interrelations of art and politics. While artists under the influence of contemporary currents in the arts reacted harshly to Jónsson’s attempts to control their output, it was clear that the politician wanted to utilize the arts for a nationalistic cause in Icelandic society and he wanted the nation’s art to stand clear from foreign art movements that he saw as unfitting for Icelandic art. His ideas therefore touched on ideas about the ethnic purity of the Icelandic national identity, that cultural artefacts were meant to reflect. Ultimately the ideas of the isolation of Icelandic art from current developments in western art were unrealistic, as the country was developing closer ties to the outside world in the Second World War.